Differential effects of glucose‐dependent insulinotropic polypeptide receptor/glucagon‐like peptide‐1 receptor heteromerization on cell signaling when expressed in HEK‐293 cells - Bashaier Al‐Zaid; Siby Chacko; Charles Ifeamalume Ezeamuzie; Moritz Bünemann; Cornelius Krasel; Tina Karimian; Peter Lanzerstorfer; Suleiman Al‐Sabah (Wiley, 2022)
Abstract The incretin hormones: glucose‐dependent insulinotropic polypeptide (GIP) and glucagon‐like peptide‐1 (GLP‐1) are important regulators of many aspects of metabolism including insulin secretion. Their receptors (GIPR and GLP‐1R) are closely related members of the secretin class of G‐protein‐coupled receptors. As both receptors are expressed on pancreatic β‐cells there is at least the hypothetical possibility that they may form heteromers. In the present study, we investigated GIPR/GLP‐1R heteromerization and the impact of GIPR on GLP‐1R‐mediated signaling and vice versa in HEK‐293 cells. Real‐time fluorescence resonance energy transfer (FRET) and bioluminescence resonance energy transfer (BRET) saturation experiments confirm that GLP‐1R and GIPR form heteromers. Stimulation with 1 μM GLP‐1 caused an increase in both FRET and BRET ratio, whereas stimulation with 1 μM GIP caused a decrease. The only other ligand tested to cause a significant change in BRET signal was the GLP‐1 metabolite, GLP‐1 (9-36). GIPR expression had no significant effect on mini‐Gs recruitment to GLP‐1R but significantly inhibited GLP‐1 stimulated mini‐Gq and arrestin recruitment. In contrast, the presence of GLP‐1R improved GIP stimulated mini‐Gs and mini‐Gq recruitment to GIPR. These data support the hypothesis that GIPR and GLP‐1R form heteromers with differential consequences on cell signaling.